Pengaruh Relaksasi Benson terhadap Penurunan Nyeri Paska Bedah pada Pasien Transurethral Resection of the Prostate. - Sueb, Sueb; Triwibowo, Cecep (Jurusan Keperawatan FIKES UNSOED, 2016)
Action postoperatively of transurethral resection of the prostate can cause pain and trauma. The use of non-pharmacological and pharmacology therapy can be used to reduce pain intensity in patients post-surgery. Relaxation Benson is a non-pharmacological therapy involving patient confidence factor for achieving health and welfare conditions is higher. The purpose of this study is to determine the effect of Benson relaxation of the reduction in pain intensity in patients with postoperative TURP. This study is a experiment with approaches randomized Pretest-Posttest Control Group Design. The sampling technique using total sampling 14 patients with TURP actions were divided into 2 groups: control group by administering analgesics and treatment groups by administering analgesics and relaxation Benson. Data were analyzed using paired t-test and independent T-Test. The results showed that administration of analgesics can not reduce pain intensity in patients TURP with a P value of 0156. Combination therapy of Benson relaxation and administration of analgesics can reduce pain intensity in patients TURP with a P value of 0.002. T independent test confirms that the combination therapy of relaxation Benson and giving analgesics can reduce pain intensity in patients TURP compared to only the provision of analgesia with a P value of 0.017. Conclusion The combination therapy Benson relaxation and giving analgesics can reduce pain intensity in patients with postoperative TURP.